Promoting Sustained Breastfeeding of Infants at Risk for Asthma: Explaining the “Active Ingredients” of an Effective Program Using Intervention Mapping - Mesters, Ilse; Gijsbers, Barbara; Bartholomew, L. Kay (Frontiers in Public Health, 2018)
Infants of parents with a history of asthma could benefit from receiving exclusive breastfeeding during the first six months after birth. This may reduce the chance of developing childhood asthma. Continuing to breastfeed for six months seems difficult to perform for many women. An educational program was developed using Intervention Mapping as a logic model to guide development, and was found successful in improving breastfeeding rates at six months postpartum, improving knowledge and attitudinal beliefs regarding breastfeeding for six months, after exposure to the program compared to controls. Intervention elements included a theory-based booklet addressed during pre- and postnatal home visits by trained assistants. This paper elucidates the inner workings of the program by systematically describing and illustrating the steps for intervention development.